1999
DOI: 10.1177/019262339902700508
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone-Induced Heart and Adipose Tissue Cell Proliferation in Mice

Abstract: Troglitazone, a thiazolidinedione, is a novel agent for the oral treatment of non-insulin-dependent (Type II) diabetes mellitus; it works by increasing cell sensitivity to available insulin. Previous studies have shown that rodents treated with high doses of troglitazone develop increased heart weight and increased interscapular brown fat. This study investigated cellular proliferation in heart and brown fat of troglitazone-treated mice as well as possible interactions with an angiotensin-converting enzyme inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Such robust action on uptake, which extends to albumin-bound NEFA (see below), appears to explain most of the twofold increase in BAT TG content, given that short-term RSG did not affect de novo lipogenesis. The higher number of competent brown fat cells resulting from increased adipogenesis (4,41) by PPAR␥ stimulation likely contributed toward increasing the ability of BAT to take up and store lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Such robust action on uptake, which extends to albumin-bound NEFA (see below), appears to explain most of the twofold increase in BAT TG content, given that short-term RSG did not affect de novo lipogenesis. The higher number of competent brown fat cells resulting from increased adipogenesis (4,41) by PPAR␥ stimulation likely contributed toward increasing the ability of BAT to take up and store lipids.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized previously that PPAR+ activators produce cardiomyocyte hypertrophy through undetermined mecha- [26,[31][32][33]. PPAR+ activators can also reduce the expression of vascular endothelial growth factor receptors, which may inhibit angiogenesis [34], as well as trigger endothelial cell apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, dosing mice at 1200 mg /kg per day for 14 days results in increased brown adipose tissue weight, but decreased white adipose tissue weight. 26 At these dose levels, there is significant accumulation of interscapular brown fat. Studies with the labelled nucleoside analogue BrdU suggested that increased brown fat deposition was a consequence of increased cell proliferation.…”
Section: Effects On Adipose Tissuementioning
confidence: 99%